2018
DOI: 10.1089/end.2017.0795
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Disease-Specific Ureteral Calculus Patient Reported Outcome Measurement Instrument

Abstract: CUSP is a patient-derived ureteral stone PROM, which can be used to measure ureteral stone disease health outcomes from the patient's point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This is different for ureteric stones, where most patients are symptomatic , highlighting the need to assess the experience of the patients with renal stone separately from ureteric stones. In conjunction with developing a ureteric stone disease‐specific PROM tool (Cambridge Ureteric Stone PROM) , we allow for a sensitive, tailored approach to assess the experience of two clinically different phases of the disease. Studying the correlation between CReSP and WISQOL will guide on complimentary benefits of using both tools.…”
Section: Discussionmentioning
confidence: 99%
“…This is different for ureteric stones, where most patients are symptomatic , highlighting the need to assess the experience of the patients with renal stone separately from ureteric stones. In conjunction with developing a ureteric stone disease‐specific PROM tool (Cambridge Ureteric Stone PROM) , we allow for a sensitive, tailored approach to assess the experience of two clinically different phases of the disease. Studying the correlation between CReSP and WISQOL will guide on complimentary benefits of using both tools.…”
Section: Discussionmentioning
confidence: 99%
“…Patient feedback data was not systematically collected in our study; however, Oderda et al 13 have previously demonstrated that Isiris ® stent removal is well-tolerated by patients. Ultimately, assessment of patients quality of life preoperatively would be a very interesting aspect to study, and this could be done using one of the specifically designed quality of life measures such as the Cambridge Ureteral Stone PROM (CUSP) 21 or the Cambridge Renal Stone PROM (CReSP) 22 for ureteric and renal stone treatments respectively, and then asking the patients to complete the questionnaires J Endolum Endourol Vol 4(1):e45-e53; April 14, 2021.This article is distributed under the terms of the Creative Commons Attribution-Non Commercial 4.0 International License. © Thakare, et al…”
Section: Discussionmentioning
confidence: 99%
“… 39 There also exists a PROMs designed to specifically assess symptom burden associated with ureteric stones, the Cambridge Ureteral Stone PROM (CUSP). 40 …”
Section: Endourological Armamentariummentioning
confidence: 99%